Wojny o granice Polski odrodzonej, 1918-1921 - Wrzosek, Mieczyslaw (Warszawa : Wiedza Powszechna, 1992)
A study of Poland's battles for its frontiers, from 1918 to 1921.
Includes bibliographical references (p. 359-[364]) and index.
Keywords: Poland. -- Wojsko Polskie -- History; Poland -- History -- Wars of 1918-1921 -- Campaigns; Poland -- History, Military -- 1918-